A conductive ternary network of a highly stretchable AgNWs/AgNPs conductor based on a polydopamine-modified polyurethane sponge1. Issue 77 (22nd August 2015) - Li, Liming; Zhu, Chunhua; Wu, Yeping; Wang, Jianhua; Zhang, Tailiang; Liu, Yu
<x xml:space="preserve">Abstract</x> A conductive ternary network structure composed of AgNWs/AgNPs based on a polydopamine-modified 3D PU sponge was fabricated, which shows excellent electromechanical ability owing to the combined effects from the ternary network.